Persepsi Siswa tentang Keterampilan Mengajar Mahasiswa Program Praktek Lapangan (PPL) Jurusan Administrasi Pendidikan UNP SE- SMK Negeri Kota Padang - Jelita Navisa; Jasrial Jasrial; Ermita Ermita; Sulastri Sulastri (Journal of Educational Administration and Leadership, 2021)
This reason for this research was based on observations and experiences during the educational field practice related to the teaching skills of students in the field practice program (PPL) of the Department of Educational Administration, Padang State University, State Vocational Schools of Padang City. This research is a quantitative descriptive type which aims to see how the teaching skills performed by PPL students of the Department of Educational Administration, Padang State University according to students’ perceptions. This study has a population of 2891 people who all have studied with PPL students, Department of Educational Administration, State University of Padang. The sampling technique used was proportional random sampling technique which obtained 102 people. This research instrument uses a Likert scale questionnaire on teaching skills consisting of 60 items. Data collected online using google form. The data collected is processed to look for an average score. From the results of data processing, it was found that the average score of teaching skills of PPL students in the Department of Educational Administration, State University of Padang in the aspect of learning opening skills was 4,13 with good criteria, the skill of explaining the material was 4,15 with good criteria, the questioning skills were 4,24 with good criteria, the skills to provide reinforcement are 3,86 with good criteria, the skills to manage classes are 4,35 with good criteria, the skills to use various teaching variations are 4,15 with good criteria, the skills to use teaching media are 3,61 with good criteria, the skill of closing learning is 4,33 with good criteria. So according to students in Padang City State Vocational Schools who study with PPL students of the Education Admistration Department, Padang State University at Padang City State Vocational High School have been carried out well.